Digital hand lettering and modern calligraphy : essential techniques plus step-by-step tutorials for scanning, editing, and creating on a tablet /: essential techniques plus step-by-step tutorials for scanning, editing, and creating on a tablet. (2019) - Kim, Shelly
No abstract available